The ranchers - Time-Life Books; Tanner, Ogden; Larry Dingman Western Fiction Collection (Library of Congress) (Alexandria, Virginia : Time-Life Books, 1977)
Describes in text and illustrations the development of large ranches in the western plains, the impact of these establishments on the economy of the area, their organization, and some famous ranches and their owners.
A life carved out of the plains -- Battling the odds and the elements -- A wave of woollybacks -- War over land and water -- Bluebloods and big money in the Badlands -- "Behold our ditches!"
Includes bibliographical references (pages 236-237) and index.
Keywords: Ranch life -- West (U.S.) -- History; Frontier and pioneer life -- West (U.S.); Ranch life; Frontier and pioneer life; West (U.S.) -- History; West (U.S.) -- History